Kapitalizm : Russia's struggle to free its economy - Brady, Rose, 1956- (Yale University Press, 1999)
Rose Brady, former Moscow bureau chief for Business Week magazine, here provides a compelling firsthand account of Russia's transition from a socialist state to a market economy. Taking us into the factories, stores, banks, markets, homes, schools, and corridors of power in Russia, she explains how the country's own brand of capitalism has evolved.